Effect of fermented noni leaf (Morinda citrifolia L.) in diets on cholesterol content of broiler chicken carcass - Syahruddin, Erman; Abbas, H.; Purwati, E.; Heryandi, Y. (Indonesian Animal Sciences Society, 2011)
Chicken meat is very nutritious. It is sometimes blamed to cause strock attack and coronary heart disease in human, because of high fat and cholesterol contents in the chicken meat. Therefore, the aim of this experiment is to evaluate the effect of fermented noni leaf levels in diets on the cholesterol content of broiler chicken carcass. The experiment was based on completely randomized design with eight experimental diets containing 0, 3, 6, 9, 12, 15, 18 and 21% of fermented noni leaf powder. All diets were formulated to contain 22% crude protein and 3000 kcal/kg. Each treatment had three replicates with ten chickens per replicate. Two hundred and forty day old unsex broiler chicks Arbor Acress were fed ad lib. for eight weeks and then sacrificed. Feed consumption, body weight gain, feed conversion ratio, and cholesterol content of carcass were taken as variable responses. Data were analyzed based on analysis of variance and orthogonal comparisons. Results showed that feed consumption, daily weight gain, FCR and carcass content were not affected by the levels of fermented noni leaf in the diet. However, cholesterol content of broiler carcass was significantly (P < 0.05) affected by the dietary treatments. Cholesterol content of the carcass was reduced processed 26.18% 73.06 to 53.76 mg/100g mg/100g chicken meat. The lowest cholesterol level was obtained by feeding the chickens with diets containing 21% fermented noni leaf. Key Words: Morinda citrifolia L., Cholesterol, Broiler Chickens